Triple Positive Solutions for a Type of Second-Order Singular Boundary Problems. (1st September 2010) - Li Li, Jiemei Jiemei; Wang Wang, Jinxiang Jinxiang
Abstract : This paper deals with the existence of triple positive solutions for a type of second-order singular boundary problems with general differential operators. By using the Leggett-Williams fixed point theorem, we establish an existence criterion for at least three positive solutions with suitable growth conditions imposed on the nonlinear term.